Synthesis and Characterization of used Oil Bio-Adsorbent Material based on Corn Husk Activated Carbon - Pelangi Eka Yuwita; Roihatur Rohmah; Moh. Mu'id Efendi (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
Used oil waste is classified as hazardous B3 waste that poses a significant environmental threat. To address the hazards posed by used oil waste, synthesizing activated carbon as an adsorbent for used oil is necessary. This research aims to synthesize and characterize activated carbon from corn husk waste as an adsorbent material for used oil. The methods employed in this research include dehydration, carbonization, and activation using HCl and NH4OH. The structure was analyzed using XRD, UV-visible spectrophotometer, and Oswald viscometer, followed by variations in mesh sizes of 60 and 100 and the addition of PEG. Based on the research results, variations in 60 and 100 mesh have nearly identical X-ray diffraction patterns, with values of 2θ at 19.2074° and 23.0729° in the 60mesh variation, and 2θ at 19.1333° and 23.2161°, which are indicative of graphite diffraction patterns as they fall within the ~25° range and match the CIF 9014004 data for phase C Graphite with space group p6/mmm. In UV-Visible spectrophotometer testing, variations of 60 mesh without PEG, 100 mesh without PEG, 60 mesh with PEG, and 100 mesh with PEG showed absorbance values of 2.3, 1.58, 1.394, and 0.966, respectively, and viscosity values of 22.089, 20.089, 21.09, and 19.21 cP. The 100mesh sample with the addition of PEG is the variation that can effectively adsorb used oil.